Cognitive neural responses in the semantic comprehension of sound symbolic words and pseudowords - Sasaki, Kaori; Kadowaki, Seiichi; Iwasaki, Junya; Pijanowska, Marta; Okamoto, Hidehiko (Frontiers in Human Neuroscience, 2023)
Introduction Sound symbolism is the phenomenon of sounds having non-arbitrary meaning, and it has been demonstrated that pseudowords with sound symbolic elements have similar meaning to lexical words. It is unclear how the impression given by the sound symbolic elements is semantically processed, in contrast to lexical words with definite meanings. In event-related potential (ERP) studies, phonological mapping negativity (PMN) and N400 are often used as measures of phonological and semantic processing, respectively. Therefore, in this study, we analyze PMN and N400 to clarify the differences between existing sound symbolic words (onomatopoeia or ideophones) and pseudowords in terms of semantic and phonological processing. Methods An existing sound symbolic word and pseudowords were presented as an auditory stimulus in combination with a picture of an event, and PMN and N400 were measured while the subjects determined whether the sound stimuli and pictures match or mismatch. Results In both the existing word and pseudoword tasks, the amplitude of PMN and N400 increased when the picture of an event and the speech sound did not match. Additionally, compared to the existing words, the pseudowords elicited a greater amplitude for PMN and N400. In addition, PMN latency was delayed in the mismatch condition relative to the match condition for both existing sound symbolic words and pseudowords. Discussion We concluded that established sound symbolic words and sound symbolic pseudowords undergo similar semantic processing. This finding suggests that sound symbolism pseudowords are not judged on a simple impression level (e.g., spiky/round) or activated by other words with similar spellings (phonological structures) in the lexicon, but are judged on a similar contextual basis as actual words.